Predominance of syntrophic bacteria, Methanosaeta and Methanoculleus in a two-stage up-flow anaerobic sludge blanket reactor treating coffee processing wastewater at high organic loading rate - Botello Suárez, Wilmar Alirio [UNESP] (2018)
The effect of the organic loading rate (OLR) on the performance and microbial composition of a two-stage UASB system treating coffee processing wastewater was assessed. The system was operated with OLR up to 18.2 g COD (L d)−1 and effluent recirculation. Methane production and effluent characteristics were monitored. The microbial composition was examined through next-generation sequencing and qPCR from the anaerobic sludge of the first reactor (R1) operated at low and high OLR. The system showed operational stability, obtaining a maximum methane production of 2.2 L CH4 (L d)−1, with a removal efficiency of COD and phenolic compounds of 84 and 73%, respectively. The performance of R1 at high OLR in steady conditions was associated with an appropriate proportion of nutrients (particularly Fe) and a marked increase of the syntrophic bacteria Syntrophus and Candidatus Cloacimonas, and acetoclastic and hydrogenotrophic methanogens, mainly Methanosaeta, Methanoculleus, Methanobacterium and Methanomassiliicoccus.